2020
DOI: 10.1111/evj.13216
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of histamine‐provoked changes in airflow using electrical impedance tomography in horses

Abstract: Background Electrical impedance tomography (EIT) generates thoracic impedance images of the lungs and has been used to assess ventilation in horses. This technique may have application in the detection of changes in airflow associated with equine asthma. Objectives The objective was to determine if histamine‐induced airflow changes observed with flowmetric plethysmography (Δflow) could also be explained using global and regional respiratory gas flow signals calculated from EIT signals. Study design Experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(41 citation statements)
references
References 26 publications
1
40
0
Order By: Relevance
“…Previous studies have identified unchanging tidal volumes during bronchoconstriction in horses. 11,25,26 The respiratory rate increased with histamine and then decreased with albuterol, whereas tidal volume did not change significantly, indicating an increase and then subsequent decrease in minute ventilation. The observed increase in respiratory rate results in a decrease in inspiratory 24,25 and expiratory time, 24 which leads to the measured increase in flow variables at stable tidal volume.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Previous studies have identified unchanging tidal volumes during bronchoconstriction in horses. 11,25,26 The respiratory rate increased with histamine and then decreased with albuterol, whereas tidal volume did not change significantly, indicating an increase and then subsequent decrease in minute ventilation. The observed increase in respiratory rate results in a decrease in inspiratory 24,25 and expiratory time, 24 which leads to the measured increase in flow variables at stable tidal volume.…”
Section: Discussionmentioning
confidence: 98%
“… 10 From the flow signal, global peak inspiratory (PIF EIT ) and global peak expiratory (PEF EIT ) flow were calculated for the whole lung for each breath. 11 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the different electrical features of the object in the sensitivity field, the ET techniques could be divided into electromagnetic tomography (EMT), electrical capacitance tomography (ECT), electrical impedance tomography (EIT), and electrical resistance tomography (ERT). Based on the principle of electromagnetic induction, the EMT can reconstruct the distribution state of the magnetic permeability for the medium in the sensitivity field [1][2][3][4][5][6]; Based on the principle of capacitance sensitivity, the ECT can reconstruct the distribution state of the dielectric constant for the medium in the sensitivity field [7][8][9][10][11][12][13][14][15][16][17]; Based on the principle of impedance sensitivity, the EIT can reconstruct the distribution state of the complex admittance for the medium in the sensitivity field [18][19][20][21][22][23][24]; Based on the principle of resistance sensing, the ERT can reconstruct the distribution state of the dielectric resistivity/conductivity for the medium in the sensitivity field [25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Electrical tomography (ET) technology consists of 4 different branches, namely, electrical impedance tomography (EIT) [8][9][10][11][12][13][14], ERT [15][16][17][18][19][20], electrical capacitance tomography (ECT) [21][22][23][24][25][26][27], and electromagnetic tomography (EMT) [28][29][30][31][32][33], among which the ERT technology is a new generation of medical imaging technology and a simplified form of the EIT technology when only the change of conductivity/resistivity of the sensitive field is considered, having three outstanding advantages of functional imaging, no damage, and medical image monitoring. Compared with other monitoring methods, ERT technology has incomparable advantages in real-time monitoring and quantitative evaluation of critical respiratory diseases.…”
Section: Introductionmentioning
confidence: 99%